Body mass trajectories, diabetes mellitus, and mortality in a large cohort of Austrian adults. Issue 49 (December 2016) - Peter, Raphael Simon; Keller, Ferdinand; Klenk, Jochen; Concin, Hans; Nagel, Gabriele
Abstract : Abstract: There are only few studies on latent trajectories of body mass index (BMI) and their association with diabetes incidence and mortality in adults. We used data of the Vorarlberg Health Monitoring & Prevention Program and included individuals (N=24, 875) with BMI measurements over a 12-year period. Trajectory classes were identified using growth mixture modeling for predefined age groups (<50, 50–65, >65 years of age) and men, women separately. Poisson models were applied to estimate incidence and prevalence of diabetes for each trajectory class. Relative all-cause mortality and diabetes-related mortality was estimated using Cox proportional hazard regression. We identified 4 trajectory classes for the age groups <50 years and 50 to 65 years, and 3 for age groups >65 years. For all age groups, a stable BMI trajectory class was the largest, with about 90% of men and 70% to 80% of women. For the low stable BMI classes, the corresponding fasting glucose levels were the lowest. The highest diabetes prevalences were observed for decreasing trajectories. During subsequent follow-up of mean 8.1 (SD 2.0) years, 2741 individuals died. For men <50 years, highest mortality was observed for steady weight gainers. For all other age-sex groups, mortality was the highest for decreasing trajectories. We found considerably heterogeneity in BMI trajectories by sex and age. Stable weight, however, was the largest class over all age and sex groups, and was associated with the lowest diabetes incidence and mortality suggesting that maintaining weight at a moderate level is an important public health goal. Abstract : Supplemental Digital Content is available in the text